OMAR SHAYÍR DÓRETIWSHILIGINDE HAYAL - QÍZLAR TEMASÍ - Davletov, B.A. (SCIENCE and SOCIETY, 2022)
The article analyzes the works of Karakalpak poet Omar Suyirbek. Poet’s songs on the theme of women are studied through artistic texts. The fate of women in his works, their stature, beauty, expression, intelligence, behavior, manners, etc. revealed.